PERENCANAAN BISNIS LALUMIERE PICTURES - Gabriella Sengkey; Petrus Pius Salamin (Prosiding Working Papers Series In Management, 2018)
LaLumiere Pictures is a business engaged in a film and television field and a part of creative, entertainment, and media industry. LaLumiere Pictures is a production house (company) that provide production services in film, TV series, and video. LaLumiere Pictures has a vision to be a superior and totality production house in helping of creating the work of “moving pictures” as media for entertainment through quality and productive creativity. LaLumiere Pictures’ mission is to participate of produce a creative work–either it a film and a TV series basis on the relevant idea, as well as the making of the balance of credibility in production process for the optimal services or even a maximal result. There’re lots of market opportunities for LaLumiere Pictures, one of those is growth average of serving/sales with 11% in a first three years–the period of development, and approximately 57,14% in the next years–the period of development. The market strategy of LaLumiere Pictures is providing product and services which adjusted to market needs; LaLumiere Pictures targeting a market who needs a service of video production and the filmmaker, either the amateur or the professional; and using traditional marketing (W-of-M) followed by the support of modern marketing (digital marketing). LaLumiere Pictures business strategy is determining the selling price based on penetration strategy with competitive–based pricing method, to offering an affordable price; the strategic management of LaLumiere Pictures using the best–cost provider while give a customer the freedom of customization according to provided services. The financial target of LaLumiere Pictures is the initial investment with the amount of Rp 331.434.500; the service income in 2018 with the amount of Rp 559.850.000 with the profit of Rp 66.674.000; and the income growth average is about 47%. Keywords: LaLumiere Picture, Production House (Company); Film, Television, and Video